Accuracy and Challenge of Using the Australian Triage Scale (ATS) in Emergency Departments - Maulida Ummi Syafa; Anggorowati Anggorowati; Henni Kusuma (Indonesian Journal of Global Health Research, 2026)
The Australian Triage Scale (ATS) is a five-level system widely used in emergency departments (EDs) to categorize patients by urgency and ensure timely care. While ATS has improved efficiency and outcomes in many settings, concerns remain regarding its accuracy, reliability, and applicability across diverse populations. This narrative review aimed to evaluate the accuracy, reliability, predictive validity, and implementation challenges of ATS in global emergency care. Methods: This review followed a structured and systematic literature selection process. A comprehensive search was conducted across six major databases (Scopus, PubMed/MEDLINE, Embase, Cochrane Library, Google Scholar, and SINTA) for studies published between 2010 and 2024. After duplicate removal, titles and abstracts were screened, followed by full-text reviews based on predefined inclusion and exclusion criteria. Methodological quality and relevance were assessed, and 25 studies were included in the final narrative synthesis. These studies were analyzed according to key themes, including accuracy, reliability, predictive validity, training interventions, and implementation challenges of the Australian Triage Scale in emergency departments. Results: Evidence showed that ATS improves outcomes such as reduced mortality and shorter ED length of stay in some contexts. Predictive validity was strongest for high-acuity patients, with a clear mortality gradient across categories. However, reliability was only slight to moderate (κ = 0.25–0.45), particularly weak in pediatric, psychiatric, and elderly trauma patients. Under-triage was frequent in gastrointestinal bleeding and geriatric trauma, while over-triage was noted in neonates and parental anxiety-driven cases. Training interventions increased accuracy up to 88.4% but decayed without reinforcement. System challenges included overcrowding, variable audit practices, and inconsistent application across hospitals. Comparative reviews found ATS effective overall but less consistent than ESI or MTS in children. A total of 25 studies met the inclusion criteria and were synthesized narratively. ATS remains a core triage framework in emergency care. Its strengths include structured prioritization and outcome prediction in adult populations, but limitations persist in special groups and resource-limited settings. Continuous training, adaptation, and decision-support integration are essential for sustaining accuracy and safety.